Aesthetic Misinformation in Local Digital Journalism: A Case Study on Editorial Bypass in Public Service News Production - Romarez, Revierda; Sembiring, Rosmaniar; Hanifah, Ummy (University of Science and Computer Technology, 2024)
The transformation of journalism in the digital age has led to the emergence of local online media platforms operating without formal editorial structures. This study investigates the news production process of a public service article published by a semi-professional online portal, focusing on how editorial routines are adapted—or bypassed—in decentralized environments. The selected article, which listed hospitals affiliated with the national health insurance program, was widely circulated yet contained factual inaccuracies that impacted readers' real-life service access. Using a qualitative case study design, the research draws on interviews with the editor, observational data, document analysis, and reader responses. The results reveal a linear, individualized editorial workflow in which a single actor handled all stages of production without verification protocols. Visual design elements such as structured layouts and official-like typography were employed to simulate credibility, resulting in what this paper terms aesthetic misinformation. While the article was produced to serve the public, the absence of institutional oversight contributed to its unreliability. The findings contribute to media and communication studies by highlighting the tension between visual legitimacy and journalistic integrity in grassroots media production. The study recommends adopting lightweight editorial standards and reflexive design practices to promote ethical information dissemination in non-institutionalized news environments.